Implementing near infrared spectroscopy in the Iberian pork industry - De Pedro E.; Núñez N.; García J.; Aparicio D.; Campos M.I.; Pérez M.D.; Fernández V.M.; Garrido A. (5. International Symposium on the Mediterranean Pig, 2007)
The objective of this paper is to summarise the research and development strategy carried out, in close cooperation with the Iberian pork industry, for implementing Near Infrared Spectroscopy as an integral part of its quality control programs and/or traceability systems. NIRS data obtained from the adipose tissue of 224 animals, using a fiber optic probe, were used to develop calibration equations to predict the four main fatty acids (C16:0, C18:0, C18:1 and C18:2) in Iberian pig adipose tissue samples. According to the precision and accuracy obtained with these equations a methodology has been implemented, at an industry-wide level, for the payment of farmers, according to the three Iberian pork commercial categories (bellota, recebo and cebo).
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)